Vocational guidance in people with special educational needs as the result of visual impairment during the transition stage from high school to advanced education - Castignani, María Laura (2011)
This work proposes to seek for the factors related to the choices that people with special educational needs make as the result of the visual impairment, during the transition stage from high school to advanced education. Therefore, we have taken into consideration that Vocational Guidance and the transition towards adulthood get specific characteristics in case of visually impaired young people, particularly in what's related to continue with advanced education. The focus of this work is to be able to clarify the existence of factors that make this transition stage easier or harder, through the observation of visually impaired and blind people who complete high school. This matter has aroused interest and concern about the strategies to follow to ensure the successful entrance and remaining in the selected advanced education. However, if we don?t know the factors involved in the described fact, it's difficult to design an appropriate intervention strategy. Then, in order to take acknowledge about the specific issues of visually impaired young people who complete high school, we chose a special school for this disability and some students who will join this project